Edukasi Kesehatan untuk Peningkatan Status Gizi dan Skrining Anemia pada Bayi Balita dalam Pengentasan Stunting - Nathalie Elischeva Kailola; Vina Zakiah Latuconsina; Rifah Zafarani Soumena; Theresia Natalia Seimahuira; Fitri Kadarsih Bandjar; Martha Melmambessy; Jerome Constantine Lekatompessy (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Stunting is often caused by inadequate maternal nutrition during pregnancy, suboptimal breastfeeding practices, delayed introduction of complementary foods, and impaired nutrient absorption due to infections. This community engagement activity aimed to improve parents' knowledge of balanced diets and conduct anemia screening among infants and toddlers in Wab and Debut Villages, Southeast Maluku Regency. The methods included interactive education sessions, distribution of educational leaflets, questionnaire administration, and assessments of nutritional status and hemoglobin levels in children. The activity was carried out over two days. Results showed that most mothers had limited knowledge of balanced nutrition for young children, although their understanding of the First 1,000 Days of Life was relatively adequate. In Wab Village, 15 out of 68 children were undernourished and 28 were anemic, while in Debut Village, 25 out of 80 children were undernourished and 26 were anemic. These findings highlight the urgent need for more intensive nutrition education and sustained interventions to improve child health in the region.